Development of Interactive Multimedia Using Problem Based Learning Model in Class VIII Integrated Science Subjects Junior High School - Hakim, Lukman; Bentri, Alwen; Hidayati, Abna; Amilia, Winanda (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2023)
This study addresses low student learning outcomes due to limited use of interactive multimedia and lack of interest in learning using the same model. The aim is to develop valid and practical interactive multimedia through a problem-based learning approach for science subjects. This research is a development research (R&D) with the ADDIE development model. The results of research on learning media development by media validator 1 were obtained " 4.95" with the category "Very Valid". While the results of the assessment of media validator 2 obtained "4.95" with the category "Very Valid", and material validators obtained "4.71" with the category "Very Valid  ". The results of the practicality test to students on interactive multimedia can be concluded that the assessment carried out by students obtained 3.51 results with the category "Practical". The results of the effectiveness test were obtained from the comparison  of pre-test and post-test  scores of  students and obtained the results of the Wilcoxon signed rank test showed that Sig.  (p value) of 0.00 < 0.05, so interactive multimedia is declared "Eeffective" because there are significant differences. It can be concluded that interactive multimedia products are suitable for use in the learning process.